EDUKASI MENJAGA KELESTARIAN LINGKUNGAN HIDUP MELALUI STORY TELLING KEPADA ANAK-ANAK DI LINGKUNGAN CILIWUNG - Marisa Puspita Sary; Vera Wijayanti; Maulina Larasati Putri; Citra Amalia Putri Sutiyono; Farah Aulia (IKATAN ALUMNI DOSEN MAGANG KEMENRISTEKDIKTI TAHUN ANGKATAN 2017, 2026)
The Ciliwung River is one of the most polluted rivers in Indonesia, which is caused by low public awareness in maintaining environmental cleanliness. This service activity aims to increase the awareness of children living around the Ciliwung River on environmental issues through an educational approach based on storytelling. The method used is community education by instilling environmental conservation values in an interactive and fun way. Through stories, children are invited to understand the impact of pollution and the importance of protecting the river ecosystem. The results of the activity showed the high enthusiasm of the participants, as well as the emergence of new enthusiasm and awareness in maintaining environmental cleanliness. This approach proved to be effective in fostering awareness from an early age, so that it is expected to form a generation that cares more about the preservation of the environment around them.